2001
DOI: 10.1016/s0921-4534(00)01520-3
|View full text |Cite
|
Sign up to set email alerts
|

Debye temperature in YBa2Cu3Ox as measured from the electron spin–lattice relaxation of doped Yb3+ ions

Abstract: The electron spin±lattice relaxation (SLR) times T 1 of Yb 3 ions were measured from the temperature dependence of electron spin resonance line width in Y 0X99 Yb 0X01 Ba 2 Cu 3 O x with dierent oxygen contents. Raman relaxation processes dominate the electron SLR. Derived from the temperature dependence of the SLR rate, the Debye temperature (H D ) increases with the critical temperature T c and oxygen content x. This relationship between T c and H D can be well understood in terms of the modi®ed Bardeen±Coop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…) and, as we have shown for Yb 3+ and Er 3+ probes in YBaCuO compounds [6,7,8], caused by the 4f-electron-phonon interaction only. To determine the dominating spin-lattice relaxation process we use the next approach.…”
Section: +supporting
confidence: 51%
“…) and, as we have shown for Yb 3+ and Er 3+ probes in YBaCuO compounds [6,7,8], caused by the 4f-electron-phonon interaction only. To determine the dominating spin-lattice relaxation process we use the next approach.…”
Section: +supporting
confidence: 51%
“…12 There have been a few EPR studies of the RE ions with non-zero orbital moment (Er and Yb) doped in cuprates. 13,14,15,16,17,18,19,20 Again, the situation with EPR is similarly contradictory as in INS studies. Some groups observed both electronic (Korringa) and phononic (Orbach) contributions to EPR relaxation.…”
Section: Introductionmentioning
confidence: 89%
“…13,16,17 While others conclude that the Korringa contribution is negligible and the interaction with lattice vibrations only is sufficient to explain the temperature dependence of the EPR linewidth in cuprates. 18,19,20 In this work we report a detailed EPR study of the Yb 3+ relaxation in YBa 2 Cu 3 O x samples with oxygen content x covering the whole doping range (6 < x < 7). By measuring the temperature dependence of the Yb 3+ EPR linewidth in a broad temperature range, it was found that both phononic and electronic mechanisms contribute to the relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of lattice vibrations on the relaxation rate is conventionally described in terms of Debye model [6] taking into account only acoustic phonons. It allows to fit the experimental EPR results adequately even for the high-temperature superconducting cuprates [20,21]. This simple approximation implies a parabolic phonon spectrum confined by the Debye frequency ω D (or corresponding Debye temperature D ) which is the one of the important parameters in solid-state physics.…”
Section: Resultsmentioning
confidence: 99%